Oral rehabilitation in victims of domestic violence and its relationship with self-esteem and quality of life - Fiedler, Fernanda Paiva; Pereira, Bárbara Lídia da Silva; Pedrosa, Simone Soares; Gauch, Lurdete Maria Rocha; Corrêa, Davi Lavareda; Nascimento, Liliane Silva do; Pedrosa, João Pedro Costa; Dias, Hercules Bezerra; Gauch, Isabelle Rocha; Corrêa, Vania Castro; Corrêa, Suelen Castro Lavareda; Uchôa, Sue Ann Lavareda Corrêa (Seven Editora, 2024)
Domestic violence is a complex problem that affects people of all ages, races, creeds and social classes, generating several complications for women. Many of the traumas resulting from violence are orofacial, causing physical and functional changes, as well as aesthetic impacts that can aggravate chronic problems, such as depression. This significantly affects the quality of life and social interaction of victims, as psychological complications negatively influence the perception of oral health. This study aims to report the humanized oral rehabilitation of a patient who is a victim of domestic violence, correlate rehabilitation treatment with self-esteem and quality of life, and encourage the interruption of domestic violence. The treatment was carried out at the Integrated Clinic III and IV of the School of Dentistry of the Federal University of Pará (UFPA), following a plan that involved several areas of Dentistry and with the patient's consent. The patient received guidance on oral hygiene and underwent procedures such as scaling, prophylaxis, extractions, endodontic treatments, composite resin restorations, intraradicular retainers, total acrylic resin crowns, and temporary upper partial dentures (PRP). It was concluded that oral rehabilitation significantly increased the patient's self-esteem and quality of life, encouraging her to complete the treatment with crowns and definitive PRPs, in addition to contributing to the interruption of cycles of domestic violence. DOI:https://doi.org/10.56238/sevened2024.014-001